IMF Research Bulletin, June 2010. (IMF Research Bulletin; IMF Research Bulletin, 2010)
This paper analyzes the link between economic growth and structural reforms. The paper highlights that as the recovery from the financial crisis firms up, many country authorities will turn their focus from short-term stabilization policies to more structural policies to spur long-term potential growth. The paper discusses that the global financial crisis has affected growth in countries of all income levels and has led to substantial output losses that in many cases could be permanent. The paper also presents a discussion on monetary policy and asset prices.